2007
DOI: 10.1111/j.1471-0528.2006.01247.x
|View full text |Cite
|
Sign up to set email alerts
|

Could a cervical occlusion suture be effective at improving perinatal outcome?

Abstract: Cervical weakness and infection have long been regarded as major causes of preterm birth. Cervical cerclage has been used extensively to reduce the risk of preterm birth arising as a result of cervical weakness, but increasing evidence suggests that the cervix plays more than just a mechanical role. Immunological function of the cervix and mucus plug is thought to be important in minimising the ingress of microbes, which can lead to chorioamnionitis and rupture of the amniotic membranes. In this review, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
1
25
0
2
Order By: Relevance
“…Noori et al. found a take‐home baby rate of 93% in a descriptive study of 53 women with at least one prior mid‐trimester loss . We found similar results in our preliminary study .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Noori et al. found a take‐home baby rate of 93% in a descriptive study of 53 women with at least one prior mid‐trimester loss . We found similar results in our preliminary study .…”
Section: Discussionsupporting
confidence: 89%
“…The procedure involved the surgical removal of the epithelial lining of the cervical canal in a similar fashion to conisation. A simpler, less traumatic technique has been developed, whereby the external cervical os is occluded using a continuous suture at the time that the cerclage is applied . In comparison with a historical cohort, we found that cerclage in which suture occlusion was applied was associated with a higher success rate (take‐home baby rate) .…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…18 Proponents hypothesized that diminished mechanical support in the cervical stroma might foster ascending infection, and act synergistically to precipitate the spontaneous preterm birth syndrome.Adescriptivestudyofthistechnique supported its beneficial role, describing a ''take-home baby'' rate of 93% in women withatleast1priormidtrimesterloss. 18 One RCT comparing the efficacy of historyindicated or ultrasound-indicated cerclage withcervicalocclusionversuscerclagewithout occlusion, however, found no difference in rates of preterm birth before 34 and 28 weeks, gestational age at delivery, ''takehome baby'' rate, or neonatal intensive care unit admission between the groups. 19 Although mode of delivery was not assessed in this study, cervical occlusion is likely associated with scarring that may preclude vaginal delivery.…”
Section: Cervical Occlusionmentioning
confidence: 99%
“…The most common pathway for intrauterine infection is the ascending route from vagina and cervix [6]. Increasing evidence suggests that cervical mucus plug plays more than just a mechanical role in protecting the fetoplacental unit against ascending infection from the vagina [7]. Although in many cases it is impossible to determine whether weakness of the cervix or ascending infection is the primary cause, application of a procedure to prevent both mechanisms seemed to be promising.…”
Section: Introductionmentioning
confidence: 99%